Effect of the movement speed of resistance training exercises on sprint and strength performance in concurrently training elite junior sprinters - Blazevich, A. J.; Jenkins, D. G. (Journal of Sports Sciences, 2002)
The aim of this study was to determine the effects of 7 weeks of high- and low-velocity resistance training on strength and sprint running performance in nine male elite junior sprint runners (age 19.0+/-1.4 years, best 100 m times 10.89+/-0.21 s; mean +/- s). The athletes continued their sprint training throughout the study, but their resistance training programme was replaced by one in which the movement velocities of hip extension and flexion, knee extension and flexion and squat exercises varied according to the loads lifted (i.e. 30-50% and 70-90% of 1-RM in the high- and low-velocity training groups, respectively). There were no between-group differences in hip flexion or extension torque produced at 1.05, 4.74 or 8.42 rad x s(-1), 20 m acceleration or 20 m 'flying' running times, or 1-RM squat lift strength either before or after training. This was despite significant improvements in 20 m acceleration time (P < 0.01), squat strength (P < 0.05), isokinetic hip flexion torque at 4.74 rad x s(-1) and hip extension torque at 1.05 and 4.74 rad x s(-1) for the athletes as a whole over the training period. Although velocity-specific strength adaptations have been shown to occur rapidly in untrained and nonconcurrently training individuals, the present results suggest a lack of velocity-specific performance changes in elite concurrently training sprint runners performing a combination of traditional and semi-specific resistance training exercises.